Implementation of Policies to Build Prosperous Papuan Generations and Families in Asmat District - Halasson Fransisco Sinurat; Muchlis Hamdi; Wirman Syafri; Mansyur Achmad; Marja Sinurat (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The purpose of this study was to determine the implementation of the BANGGA Papua policy in the Asmat district, Papua Province. The research method used is a descriptive qualitative approach, with the aim of presenting a complete picture of the problem under study. Data collection by interviews, observation, documentation studies and data analysis techniques through data reduction and drawing conclusions with a total of 42 informants. The results and discussion of the implementation of the BANGGA Papua policy (Building a Prosperous Papuan Generation and Family) in Asmat District, Papua Province, explain that the productivity of the BANGGA Papua policy, as seen from the number of achievements of the target group of beneficiary communities, has not been productive because the target beneficiaries have not been achieved due to the cessation of the BANGGA Papua program which has not been running for five years. Then from the linearity dimension seen from the procedure, time, cost, place and implementation it can be said that the implementation has been linear or in accordance with the procedure, cost, place and implementer, although in terms of the time aspect the implementation of the BANGGA Papua program has not been appropriate. The existence of delays and delays in several stages of the BANGGA Papua program implementation resulted in the achievement of program targets not being achieved. While the efficiency of the implementation of the BANGGA Papua policy, seen from assets, funds and technology, is in accordance with the design of the Governor of Papua Regulation Number 23 of 2018 concerning the Program to Build a Prosperous Papuan Generation and Family.